2021
DOI: 10.1155/2021/6843828
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Mechanism of Zishen Yutai Pills on Polycystic Ovary Syndrome: A Network Pharmacology and Molecular Docking Approach

Abstract: Background. Zishen Yutai Pills (ZSYTP) is a prescription based on traditional Chinese medicine used to treat kidney-deficient pattern in traditional Chinese medicine. It is also widely used clinically for the treatment of polycystic ovary syndrome (PCOS) with positive results. This study aims to explore the potential pharmacological mechanism of ZSYTP for the treatment of PCOS by a network pharmacology approach. Methods. Compounds were collected from the Traditional Chinese Medicine Systems Pharmacology Databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Zishen Yutai pill is a famous prescription for the prevention and treatment of threatened abortion. In this formula, dodder, mulberry, Atractylodes Rhizoma, Eucommia ulmoides, and Ticrup are used together to nourish the liver and kidneys, Qi, and Yuan; ginseng, Rehmannia glutinosa, and Polygonum multiflorum are used to invigorate the spleen and Qi and nourish the blood to relieve miscarriage [ 19 ]. Modern research has also confirmed that Zishen Yutai pills can promote ovarian hormone secretion, ovulation, ovarian function, and uterine growth and development as well [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zishen Yutai pill is a famous prescription for the prevention and treatment of threatened abortion. In this formula, dodder, mulberry, Atractylodes Rhizoma, Eucommia ulmoides, and Ticrup are used together to nourish the liver and kidneys, Qi, and Yuan; ginseng, Rehmannia glutinosa, and Polygonum multiflorum are used to invigorate the spleen and Qi and nourish the blood to relieve miscarriage [ 19 ]. Modern research has also confirmed that Zishen Yutai pills can promote ovarian hormone secretion, ovulation, ovarian function, and uterine growth and development as well [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Binding between the active compound and the protein was performed using AutoDock Vina (https://vina.scripps.edu/), and the docking results were visualized using PyMOL (https://www.computabio.com/applications-of-pymol-software.html?gclid=Cj0KCQiAjbagBhD3ARIsANRrqEuKqweb76cXwtkfPu3PRFkqbTE0mOsbcO8-y8s7X35OJVQOrDwxdWIaArt1EALw_wcB) and Autodock Tools 1.5.7 (https://ccsb.scripps.edu/mgltools/). [22–25]…”
Section: Methodsmentioning
confidence: 99%
“…KNPK treatment of PCOS may be related to the activation of the APN/p38MAPK signaling pathway ( 42 ). The pharmacological effects of Zishen Yutai Pills (ZSYTP) on PCOS may be related to the HIF-1 signaling pathway, IR, and gene expression such as RNA splicing ( 114 ). ETAQC can upregulate the expression of p-AKT and GLUT4 in ovarian GCs and improve the degree of IR in ovarian tissue, thereby improving the quality of IVF-ET in PCOS patients ( 115 ).…”
Section: The Mechanism Of Tcm In the Treatment Of Pcosmentioning
confidence: 99%